Kognitivno-vedenjska terapija pri otrocih in mladostnikih s kronično bolečino - Stropnik, Staša (Psihološka obzorja (Ljubljana), 2020)
Chronic or recurrent pain in childhood is a common phenomenon, which psychologists encounter in their work within a multidisciplinary care team. In this article, we try to shed some light on the theoretical background and practical guidelines when dealing with chronic pain in children and adolescents. To understand chronic pain properly, biological/physiological, cognitive, emotional, behavioural and social factors need to be taken into consideration. In the first part of the article, we try to summarize the results of recent studies on the connection between these factors and the development of chronic pain. We highlight the theory of understanding and treating chronic pain in children and adolescents based on cognitive-behavioural theory. The second part of the article deals with the methods of cognitive-behavioural therapy for assessing and monitoring pain, psychoeducation, and specific cognitive and behavioural techniques in a systematic and practical fashion.
Keywords: adolescents; children; chronic pain; cognitive behavior therapy; kognitivno vedenjska terapija; kronična bolečina; mladostniki; otroci